Ecologia reprodutiva, comportamento acústico e territorial de uma perereca neotropical (Hypsiboas goianus) no Brasil Central - Dias, Tailise Marques (2015)
In anurans, acoustic communication is related to many different behaviors, either reproductive or territorial. In this sense, this study investigated the reproduction and the acoustic and territorial behavior of Hypsiboas goianus. The study was performed in the Floresta Nacional de Silvânia, municipality of Silvânia, state of Goiás, Brazil. Firstly, we investigated the use of calling sites, the calling pattern of the males along the night and the within-individual variation of the acoustic parameters along the night. We found a positive relationship between male snout-vent length and their distance from the water. The males emitted more aggressive calls at the early hours of the night and the number of advertisement calls emitted increased in the middle of the night. Besides, the repetition rate and interval between notes varied along the night. Additionally, we investigated the reproductive ecology and the dynamics of the territorial behavior of H. goianus. We found no relationship between the size of the female and clutch size, and also between egg size and number of eggs. Matings were not assortative. We also performed two territoriality experiments, which included manipulation of the distance between males and the placement of intruder males next to an established resident. In both experiments the number of calls emitted was influenced by size, and physical combat was rare. The results from this study show that male H. goianus maintain a reproductive strategy along the night and that, for this species, acoustic communication is greatly important in different social contexts.